2022
DOI: 10.1021/acs.langmuir.1c02999
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insight into Dye–Surfactant Interaction at Premicellar Concentrations: A Combined Two-Photon Absorption and Molecular Dynamics Simulation Study

Abstract: Both electrostatic and hydrophobic interactions play pivotal roles in ligand−surfactant binding interaction, especially for ionic surfactants. While much studies have been reported in the micellar region, less attention has been paid on such interactions at a low (premicellar) surfactant concentration. We here study the interaction between the cationic dye rhodamine 6G (R6G) with surfactants of different charge types: anionic SDS, cationic CTAB, and nonionic Tx 100 using absorption and emission spectroscopy. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…However, upon comparison, it was noticed that the extent of cyanide-mediated fluorescence quenching was more prominent with P2 compared to P1 both in the presence of S1 and S2 surfactants (Figure c). This might be due to the larger hydrophobic residue for P2 , which forces the molecules of P2 to be buried in the relatively hydrophobic region . Further, the sensitivity toward CN – ions was compared between S1 and S2 surfactants for both P1 and P2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, upon comparison, it was noticed that the extent of cyanide-mediated fluorescence quenching was more prominent with P2 compared to P1 both in the presence of S1 and S2 surfactants (Figure c). This might be due to the larger hydrophobic residue for P2 , which forces the molecules of P2 to be buried in the relatively hydrophobic region . Further, the sensitivity toward CN – ions was compared between S1 and S2 surfactants for both P1 and P2 .…”
Section: Resultsmentioning
confidence: 99%
“…This might be due to the larger hydrophobic residue for P2, which forces the molecules of P2 to be buried in the relatively hydrophobic region. 42 Further, the sensitivity toward CN − ions was compared between S1 and S2 surfactants for both P1 and P2. For both P1 and P2 compounds, it was observed that the degree of fluorescence quenching was larger in the case of surfactant S2.…”
Section: Development Of Dye-surfactant Composite Materialsmentioning
confidence: 99%
“…MD simulation is a classic method to gain a better understanding of the dye-surfactant interaction [42]. Thus, we used this method to analyze the interactions of RBB KN-R with DTAB, TTAB, and CTAB.…”
Section: Simulations Of Interactions Of Rbb Kn-r With Dtab Ttab and Ctabmentioning
confidence: 99%
“…By identifying the most promising adsorbents or drug candidates through simulations, researchers can reduce the number of experiments that need to be carried out experimentally, saving time and resources. The importance of in silico studies for designing and optimizing adsorbent materials for practical applications cannot be overstated, as several studies have shown that they provide a comprehensive understanding of the sorption behavior of the system. , …”
Section: Introductionmentioning
confidence: 99%